Pore filling type anion exchange membrane, preparation method thereof and water electrolysis hydrogen production device
Through the design of the pore-filled anion exchange membrane, the pretreated polyethylene porous separator and biphenylpiperidone-styrene are used to solve the instability of the anion exchange membrane under alkaline conditions, achieving higher mechanical and dimensional stability, and improving electrolytic water performance.
Patent Information
- Application Number
- CN202411734434.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-25
AI Technical Summary
The existing anion exchange membrane is unstable under alkaline conditions, and its mechanical properties and dimensional stability are insufficient, which affects the long-term use of electrochemical devices.
A pore-filled anion exchange membrane is used to form a huge network structure through heat cross-linking reaction between the pretreated polyethylene porous separator and biphenyl piperidone-styrene to form a large network structure to enhance the stability of the membrane.
The stability and density of the pore-filled anion exchange membrane are achieved, and its performance in electrolytic water is improved, including good stability, airtightness, conductivity and alkali resistance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure FDA0005161407250000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ion exchange membranes, and in particular to a pore-filling anion exchange membrane, a preparation method thereof, and a water electrolysis hydrogen production device. Background Art
[0002] As environmental protection issues become increasingly prominent, the development of technologies such as water electrolysis for hydrogen production, flow batteries, fuel cells, electrochemical ammonia synthesis, carbon dioxide reduction, salt difference energy conversion, electrodialysis, lithium extraction from salt lakes, and wastewater treatment has attracted much attention. In the development of the above technologies, polyelectrolyte membrane materials play the role of blocking the positive and negative electrodes, while allowing ions to selectively conduct across the membrane to form a complete current loop. The performance of polyelectrolyte membrane materials directly determines the technical parameters of electrochemical devices and their use processes. Therefore, it is very necessary to develop polyelectrolyte membrane materials with high ion selectivity, high ion conductivity, long service life, and good mechanical properties.
[0003] In recent years, researchers have made great efforts to regulate polymer skeletons in order to develop high-performance anion exchange membranes (AEMs). For example, polyolefins, polystyrenes, polyethersulfones, and poly(etherketones) have been developed as polymer skeletons for anion exchange membranes; cationic groups such as pyrazolium cations, imidazolium cations, and metal coordination cations have been developed to regulate polymer skeletons. However, these materials show many instabilities under alkaline conditions, and there are degradation reactions in the above cationic groups, including Hofmann degradation and nucleophilic substitution reactions. In addition, studies have shown that the main chain of polyarylether is easily cleaved under alkaline conditions, while polymers without ether main chains and piperidone structures are excellent alkali-resistant anion exchange membrane materials. However, despite significant progress in the alkali resistance of AEMs, most of these membranes still have deficiencies in physical properties, such as mechanical durability, tensile strength below 50MPa, elongation at break below 20%; in dimensional stability, such as polybiphenylpiperidone has a high expansion rate (>200%) at 80°C. The poor mechanical properties and dimensional stability of AEMs will directly affect the long-term use of the entire electrochemical device.
[0004] In order to improve the mechanical stability and dimensional stability of AEMs, researchers have used a variety of modification methods, including cross-linking, branched copolymerization, and "pore filling" composite materials. In contrast, the "pore filling" composite technology is considered to be the most effective way to combine ionic polymers with porous substrates to create mechanically strong and durable materials, because the porous substrates provide excellent mechanical properties and chemical stability. However, due to the significant differences between ionic polymers and porous substrates, such as hydrophilicity and hydrophobicity, the complete wetting of ionic polymer solutions in hydrophobic substrates and the stable composite of the two phases have become key issues to be solved in the research.
[0005] Therefore, it is of great significance to study and develop a new anion exchange membrane to solve the above problems. Summary of the invention
[0006] In view of this, the technical problem to be solved by the present invention is to provide a pore-filled anion exchange membrane and a preparation method thereof and a water electrolysis hydrogen production device. The pore-filled anion exchange membrane is stable and dense, has good stability, air tightness, high conductivity and alkali resistance and excellent water electrolysis performance.
[0007] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] The present invention provides a pore-filling anion exchange membrane, which is prepared by thermal crosslinking reaction between a pretreated polyethylene porous membrane and the biphenyl piperidine ketone-styrene shown in Formula 1 located in the pores of the membrane;
[0009] The polyethylene porous diaphragm is pretreated by soaking in an alcohol solvent;
[0010]
[0011] Wherein, nx and x are the degree of polymerization, 1≤n≤1000, 0.1≤x / (nx)≤1.
[0012] In the pore-filling anion exchange membrane described in the present invention, the pretreated polyethylene porous membrane and the biphenyl piperidine ketone-styrene shown in Formula 1 form a huge network structure after thermal cross-linking reaction. The cross-linked product with the network structure is tightly combined with the pretreated polyethylene porous membrane in a "physical interlocking" manner, thereby enhancing the stability of the biphenyl piperidine ketone-styrene shown in Formula 1 in the pretreated polyethylene porous membrane (substrate), so that the pore-filling anion exchange membrane has better performance in electrolyzed water.
[0013] The thermal cross-linking reaction is specifically that the olefin side chain in the biphenyl piperidine ketone-styrene shown in Formula 1 and the pretreated polyethylene porous separator are cross-linked through carbon-carbon double bonds.
[0014] Preferably, the temperature of the thermal crosslinking reaction is 50°C-120°C, more preferably 70°C-90°C. In some specific embodiments of the present invention, the temperature is preferably 80°C.
[0015] Preferably, in the present invention, the porosity of the pretreated polyethylene porous membrane is 30%-80%; more preferably, 40%-60%; and further preferably, 42%.
[0016] The thickness of the pretreated polyethylene porous membrane is 10-100 μm, more preferably 10-50 μm, and further preferably 12 μm.
[0017] In some specific embodiments of the present invention, the biphenyl piperidone-styrene shown in Formula 1 is represented by polybiphenyl piperidone-30% styrene (ie, the grafting rate of styrene is 30%) and has the following structure:
[0018]
[0019] Preferably, the alcohol solvent is selected from one or more of ethanol, methanol and isopropanol.
[0020] In the present invention, the pore-filling anion exchange membrane can be represented by a polyethylene-polybiphenyl piperidone-30% polystyrene (PE-pBP-30%) composite membrane.
[0021] The present invention also provides a method for preparing the above-mentioned pore-filling anion exchange membrane, comprising the following steps:
[0022] (1) mixing biphenyl, N-methyl-4-piperidone, trifluoromethanesulfonic acid, trifluoroacetic acid and a solvent, and reacting them in an ice bath to obtain polybiphenylpiperidone;
[0023] (2) mixing the polybiphenyl piperidone obtained in step (1), p-chloromethyl styrene and a solvent for reaction, and after the reaction is completed, adding iodomethane and potassium carbonate to the reaction system to perform a light shielding reaction to obtain the polybiphenyl piperidone-styrene shown in formula 1;
[0024] (3) mixing the poly(biphenyl piperidone)-styrene represented by Formula 1 with a solvent and degassing the mixture to obtain a casting solution;
[0025] (4) The casting solution is dropped onto the pretreated polyethylene porous diaphragm, heated to carry out a thermal crosslinking reaction, and dried to obtain the pore-filling anion exchange membrane according to any one of claims 1 to 5.
[0026] The present invention synthesizes a polybiphenyl-piperidone main chain without an ether bond by a trifluoromethanesulfonic acid and trifluoroacetic acid catalytic polymerization method, and grafts different proportions of p-chloromethylstyrene on the side chain, thereby obtaining a polybiphenyl-piperidone-styrene having a structure shown in Formula 1. Then, the polybiphenyl-piperidone-styrene having a structure shown in Formula 1 is prepared into a casting liquid, and slowly dripped onto a pretreated polyethylene porous diaphragm, and then heated to induce a cross-linking reaction between the polybiphenyl-piperidone-styrene shown in Formula 1 and the carbon-carbon double bonds in the base polyethylene porous diaphragm, and after drying, the pore-filling anion exchange membrane of the present invention is obtained.
[0027] Preferably, the molar ratio of biphenyl to N-methyl-4-piperidone in step (1) is 1:(1.0-1.5); more preferably 1:(1.0-1.2). In some specific embodiments of the present invention, it is preferably 1:1.
[0028] Preferably, the molar ratio of biphenyl to trifluoromethanesulfonic acid in step (1) is 1:(6-12); more preferably 1:(7-11). In some specific embodiments of the present invention, it is preferably 1:7. Preferably, the volume ratio of trifluoromethanesulfonic acid to trifluoroacetic acid in step (1) is 1:(0.01-0.1); more preferably 1:(0.05-0.1); further preferably 1:0.1.
[0029] The solvent in step (1) includes but is not limited to dichloromethane and the like.
[0030] The reaction time in the ice bath in step (1) is preferably 12-24 hours.
[0031] The step (1) is to react in an ice bath until the viscosity of the reaction system becomes high, and then the reaction is completed and then the separation and post-treatment are also included.
[0032] The post-separation treatment is preferably to slowly pour the reaction solution into water to precipitate the polymer, and then wash and dry it several times to obtain the poly(biphenyl piperidine ketone) in a white powder. Preferably, the molar ratio of p-chloromethylstyrene to poly(biphenyl piperidine ketone) in step (2) is (0.1-1):1.
[0033] The reaction temperature in step (2) and the light shielding reaction are both room temperature; the reaction time is preferably 24-48 hours.
[0034] The solvent in step (2) includes, but is not limited to, dimethyl sulfoxide, N-methylpyrrolidone, NN-dimethylformamide, etc. In some specific embodiments of the present invention, dimethyl sulfoxide is used.
[0035] After the light shielding reaction in step (2) is completed, post-processing such as separation is also included.
[0036] The separation is specifically to slowly pour the solution after the reaction in step (2) into acetone, wash, filter and dry to obtain the product, namely the polybiphenyl piperidone-styrene shown in formula 1.
[0037] The above room temperature is preferably 10° C.-30° C. In the present invention, preferably, the concentration of the poly(biphenyl piperidone ketone-styrene) represented by formula 1 in the casting solution of step (3) is 2wt%-10wt%.
[0038] The solvent in step (3) includes, but is not limited to, dimethyl sulfoxide, N-methylpyrrolidone, NN-dimethylformamide, etc. In some specific embodiments of the present invention, dimethyl sulfoxide is used.
[0039] In the above preparation method, the pretreatment method of the polyethylene porous diaphragm in step (4) is specifically as follows:
[0040] The polyethylene porous membrane is immersed in an alcohol solvent to clean the impurities inside the pores, thereby improving the hydrophilicity of the polyethylene porous membrane.
[0041] The pretreated polyethylene porous diaphragm is laid flat on a glass plate. Then, the casting solution is dripped onto the surface so that the pores are filled with the casting solution. Finally, the pore-filling anion exchange membrane is obtained by heating to induce a thermal crosslinking reaction, washing and drying.
[0042] The present invention has no particular limitation on the washing and drying of the above steps (1), (2) and (4), and any washing and drying method well known to those skilled in the art may be used.
[0043] In the present invention, the washing method is pure water washing, and the drying method is vacuum drying.
[0044] The preparation method of the pore-filling anion exchange membrane described in the present invention effectively improves the density of the pore-filling anion exchange membrane through the synergistic effect of "physical interlocking" and pretreatment of the hydrophilicity of the base polyethylene porous diaphragm, and at the same time, enables it to have excellent water electrolysis performance, good stability, air tightness, high conductivity and alkali resistance in water electrolysis applications.
[0045] The above preparation method is simple, efficient and suitable for large-scale industrial production.
[0046] The present invention also provides a device for producing hydrogen by electrolyzing water, comprising the above-mentioned pore-filling anion exchange membrane or the pore-filling anion exchange membrane prepared by the above-mentioned preparation method.
[0047] Preferably, the water electrolysis hydrogen production device includes a membrane electrode, bipolar plates arranged in sequence, and a sealing element.
[0048] Wherein, the membrane electrode comprises a gas diffusion layer, a catalyst layer and the anion exchange membrane of the present invention;
[0049] Preferably, the electrolyte of the water electrolysis hydrogen production device is a KOH solution with a concentration of 0.1-1 mol / L.
[0050] The present invention also provides the use of the pore-filling anion exchange membrane or the pore-filling anion exchange membrane prepared by the above-mentioned preparation method in fuel cells and liquid flow batteries.
[0051] Compared with the prior art, the pore-filling anion exchange membrane provided by the present invention is prepared by thermal crosslinking reaction of a pretreated polyethylene porous membrane and biphenyl piperidine ketone-styrene shown in Formula 1 located in the pores thereof, wherein 1≤n≤1000, 0.1≤x / (nx)≤1; the polyethylene porous membrane is pretreated by immersion in an alcohol solvent. The pore-filling anion exchange membrane is stable and dense, and has good stability, air tightness, high conductivity and alkali resistance, and excellent water electrolysis performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 is the H-NMR spectrum of polybiphenyl piperidone-30% styrene (PBP-30%) in Example 1;
[0053] Figure 2 This is a physical picture of the PE-pBP-30%-OH composite membrane in Example 1;
[0054] Figure 3 It is an electron microscope cross-sectional view of the PE-pBP-30%-OH composite membrane in Example 1;
[0055] Figure 4 This is a hydrogen gas tightness diagram of the PE-pBP-30%-OH composite membrane in Example 1;
[0056] Figure 5 The conductivity performance diagram of the PE-pBP-30%-OH composite membrane in Example 1;
[0057] Figure 6 is a conductivity degradation stability performance diagram of the PE-pBP-30%-OH composite membrane in Example 1;
[0058] Figure 7 The performance diagram of the polarization curve of the PE-pBP-30%-OH composite membrane in Example 1 based on water electrolysis at different temperatures; Figure 8 This is a graph showing the stability of water electrolysis of the PE-pBP-30%-OH composite membrane in Example 1 at constant temperature and constant current density. DETAILED DESCRIPTION
[0059] In order to further illustrate the present invention, the pore-filling anion exchange membrane, the preparation method thereof, and the water electrolysis hydrogen production device provided by the present invention are described in detail below in conjunction with embodiments.
[0060] Example 1
[0061] (I) Preparation method of pore-filled composite membrane based on polyethylene-polybiphenyl piperidone-30% styrene (30% is grafting ratio) (PE-pBP-30%)
[0062] (1) Dissolve 1.542 g (10 mmol) of biphenyl and 1.13 g (10 mmol) of N-methyl-4-piperidone in 50 mL of dichloromethane and stir at 0°C for 30 minutes; then dropwise add 5 mL of trifluoromethanesulfonic acid and 0.5 mL of trifluoroacetic acid for about 2 hours; then continue to stir at 0°C for 24 hours until the solution becomes viscous. Wash the viscous solution with pure water and vacuum dry to obtain white powder polybiphenylpiperidone.
[0063] (2) Disperse the white powder polybiphenyl piperidone in 50 mL of dimethyl sulfoxide; add 0.458 g (3 mmol) of p-chloromethyl styrene, and stir at room temperature for 24 hours; then add 1.42 g (10 mmol) of iodomethane and 1.382 g (10 mmol) of potassium carbonate, and continue stirring for 24 hours; then wash the solution with pure water, and vacuum dry to obtain a yellow powder, i.e., polybiphenyl piperidone-30% styrene ( 1 H NMR spectrum Figure 1 shown).
[0064] (3) dissolving 1 g of polybiphenyl piperidone-30% styrene polyelectrolyte in 20 ml of dimethyl sulfoxide to prepare a polybiphenyl piperidone-30% styrene solution, and performing a degassing treatment to obtain a casting solution;
[0065] (4) Cut a 10x10cm porous polyethylene (PE) membrane (with a porosity of 42% and a thickness of 12 μm), soak it in an isopropanol solution for 24 hours, take it out and lay it flat on a glass plate, turn on the heating plate to 80°C, drop the polybiphenyl piperidine ketone-30% styrene solution prepared above on the porous PE membrane, continue heating for 24 hours and then dry it, and obtain a polyethylene-polybiphenyl piperidine ketone-30% polystyrene (PE-pBP-30%) pore filling composite membrane through thermal crosslinking reaction. PE-pBP-30% was soaked in a 1 mol / L sodium hydroxide aqueous solution for 24 hours, then taken out and repeatedly washed with pure water to obtain a counterion of OH - The alkaline anion exchange membrane PE-pBP-30%-OH, the actual photo is as follows Figure 2 shown.
[0066] (II) Application of PE-pBP-30%-OH composite membrane in hydrogen production by anion exchange membrane water electrolysis
[0067] The pore-filled composite membrane of ethylene-polybiphenyl piperidone-30% polystyrene (PE-pBP-30%-OH) prepared in the above method was used for structural characterization.
[0068] (1) SEM cross-section characterization
[0069] The prepared PE-pBP-30%-OH was dried in an oven, cut into a certain size, and fractured with liquid nitrogen. The composite morphology of the polymer cross section was observed and analyzed using a scanning electron microscope. The results are as follows: Figure 3 As shown, its cross section shows a nearly dense structure.
[0070] (2) Air tightness test
[0071] The barrier property of PE-pBP-30%-OH to hydrogen at different pressures was measured by constant pressure-variable volume method. The prepared composite film was assembled in the air tightness test, and different gas pressures (such as 2bar-5bar) were set. After stabilization for 1h, the gas permeability was recorded and measured by a soap bubble flowmeter and a stopwatch. The results are shown in the figure. Figure 4 As shown, the results show that the hydrogen permeability is low at different pressures. The membrane still maintains integrity at 5 bar, and the measured hydrogen permeation flux is 3.7 Barrer.
[0072] (3) Conductivity and alkali resistance test of PE-pBP-30%-OH composite membrane
[0073] (3.1) OH of the PE-pBP-30%-OH membrane obtained in (a) - The ionic conductivity is detected by four-electrode AC impedance method to obtain the hydroxyl ion conductivity curve, as shown in Figure 5 As shown in Figure 2, it can be seen that the hydroxyl ion conductivity of PE-pBP-30%-OH membrane at 30℃-80℃ is 15-42mS cm -1 .
[0074] (3.2) The OH- ion conductivity of the PE-pBP-30%-OH membrane obtained in (a) was tested for alkaline resistance. Figure 5 As shown. It can be seen that the OH- ion conductivity of PE-pBP-30%-OH membrane is stable under 1M sodium hydroxide and 80℃. Figure 6 shown.
[0075] (4) Water electrolysis performance and stability test of PE-pBP-30%-OH composite membrane
[0076] (4.1) Conducting water electrolysis polarization curve test on the PE-pBP-30%-OH composite membrane obtained in (i). The water electrolysis test device was assembled in the order of electrode plate-gas diffusion layer-catalyst layer-PE-pBP-30%-OH membrane-catalyst layer-gas diffusion layer-electrolysis plate. The two-electrode electrolyte used 1M KOH solution. The electrochemical workstation was connected to conduct water electrolysis polarization curve test. The current density at different temperatures was tested to evaluate the water electrolysis performance of the PE-pBP-30%-OH composite membrane. The results are shown in Figure 4. Figure 7The results show that the current density of the composite film can reach 1.5A cm at 80°C and 2V. -2 .
[0077] (4.2) The electrolytic water stability test of the PE-pBP-30%-OH composite membrane obtained in (a) was carried out. According to the assembly method shown in (4.1), the electrolyte of the two electrodes was 1M KOH solution, and the electrolyte was kept at a constant temperature of 60°C and a constant current density of 500mA cm -2 The continuous water electrolysis test was carried out under the condition of 100 ℃ and 100 ℃, the voltage change trend was detected, and the stability of water electrolysis of the prepared composite membrane was evaluated. The results are as follows: Figure 8 As shown, the results show that at 500mA -2 After 600h of water electrolysis test, the voltage only increased by 0.25mV h -1 , with good stability.
[0078] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A pore-filling anion exchange membrane, characterized in that: The method is prepared by thermal crosslinking reaction between a pretreated polyethylene porous membrane and the biphenyl piperidone-styrene shown in Formula 1 located in the pores of the membrane; The polyethylene porous diaphragm is pretreated by soaking in an alcohol solvent; Wherein, nx and x are the degree of polymerization, 1≤n≤1000, 0.1≤x / (nx)≤1.
2. The pore-filling anion exchange membrane according to claim 1, characterized in that: The temperature of the thermal crosslinking reaction is 50°C-120°C.
3. The pore-filling anion exchange membrane according to claim 1, characterized in that: The porosity of the pretreated polyethylene porous diaphragm is 30%-80%; The thickness of the pretreated polyethylene porous membrane is 10-100 μm.
4. The pore-filling anion exchange membrane according to claim 1, characterized in that: The alcohol solvent is selected from one or more of ethanol, methanol and isopropanol.
5. The method for preparing a pore-filling anion exchange membrane according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) mixing biphenyl, N-methyl-4-piperidone, trifluoromethanesulfonic acid, trifluoroacetic acid and a solvent, and reacting them in an ice bath to obtain polybiphenylpiperidone; (2) mixing the polybiphenyl piperidone obtained in step (1), p-chloromethyl styrene and a solvent for reaction, and after the reaction is completed, adding iodomethane and potassium carbonate to the reaction system to perform a light shielding reaction to obtain the polybiphenyl piperidone-styrene shown in formula 1; (3) mixing the poly(biphenyl piperidone)-styrene represented by Formula 1 with a solvent and degassing the mixture to obtain a casting solution; (4) The casting solution is dropped onto the pretreated polyethylene porous diaphragm, heated to carry out a thermal crosslinking reaction, and dried to obtain the pore-filling anion exchange membrane according to any one of claims 1 to 4.
6. The preparation method according to claim 5, characterized in that: The molar ratio of biphenyl to N-methyl-4-piperidone in step (1) is 1:(1.0-1.5); The molar ratio of biphenyl to trifluoromethanesulfonic acid in step (1) is 1:(6-12); The volume ratio of trifluoromethanesulfonic acid to trifluoroacetic acid in the step (1) is 1:(0.01-0.1).
7. The preparation method according to claim 5, characterized in that: The molar ratio of p-chloromethylstyrene to polybiphenyl piperidone in the step (2) is (0.1-1):
1.
8. The preparation method according to claim 5, characterized in that: The concentration of the poly(biphenyl piperidone-styrene) represented by formula 1 in the casting solution of step (3) is 2 wt % to 10 wt %.
9. A hydrogen production device by electrolysis of water, characterized in that: The invention comprises the pore-filling anion exchange membrane according to any one of claims 1 to 4 or the pore-filling anion exchange membrane prepared by the preparation method according to any one of claims 5 to 8.
10. Use of the pore-filling anion exchange membrane according to any one of claims 1 to 4 or the pore-filling anion exchange membrane prepared by the preparation method according to any one of claims 5 to 8 in fuel cells and liquid flow batteries.
Citation Information
Patent Citations
Composite anion exchange membrane preparation method
CN103881132A
Polyarylpiperidine anion exchange membrane and preparation method and application thereof
CN111921566A
Anion exchange polymer as well as preparation method and application thereof
CN113801300A
Preparation method and application of cryptand cross-linked anion exchange membrane based on polyarylene piperidine copolymer
CN115594807A
Novel poly (spirobisindane-aryl piperidinium) copolymer ionomer, anion exchange membrane and preparation method of novel poly (spirobisindane-aryl piperidinium) copolymer ionomer
CN118613526A
Cited By
A method for preparing a pore filling type composite separator for hydrogen production by alkaline water electrolysis
CN122610149A